Bone repair material, preparation method and application thereof

CN120324674BActive Publication Date: 2026-10-09SHANGHAI SEME CELL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510323408.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2026-10-09
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

然而,单一的脂肪脱细胞基质骨修复材料在机械强度和骨诱导性方面仍有待提高

Benefits of technology

[0056] (1) The composite bone repair material prepared by the present invention is derived from human adipose tissue and decellularized matrix is ​​obtained through a series of treatments. It is completely humanized. Compared with animal-derived tissue matrix, human-derived material has good biocompatibility, which greatly reduces the immune rejection and inflammatory response in the body after material implantation, and improves the patient's comfort and treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120324674B_ABST
    Figure CN120324674B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of biomedical materials, in particular to a bone repair material and a preparation method and application thereof. The preparation method of the bone repair material comprises the following steps: removing cells from sterilized fat tissues by using a supercritical fluid method to obtain a decellularized fat matrix; crushing the decellularized fat matrix to obtain decellularized fat matrix fibers; mixing the decellularized fat matrix fibers with calcium hydrogen phosphate at a mass ratio of 1:(1-10) to obtain a mixed material; and performing sterilization and freeze-drying on the mixed material after compression molding to obtain the bone repair material. According to the specific process, the decellularized fat matrix is compounded with calcium hydrogen phosphate to obtain a bone repair material which has excellent biocompatibility, bone induction and bone conduction. Experimental results show that the material can significantly improve the bone repair ability and promote bone tissue regeneration, and provides a new effective solution for bone defect repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a bone repair material, its preparation method, and its application. Background Technology

[0002] Natural bone is a mineralized connective tissue composed of cells and an extracellular matrix. In terms of composition, the extracellular matrix contains organic components, inorganic components, and bioactive molecules. The main organic component is type I collagen, and the main inorganic component is calcium hydrogen phosphate. Autologous bone grafting is considered the "gold standard" of bone transplantation; however, it has drawbacks such as limited bone resources and the need for additional surgery. Currently, most artificial bone on the market is made from inorganic materials. Artificial bone materials have many shortcomings in promoting bone regeneration, such as poor biocompatibility, slow degradation rate, and low bone fusion efficiency.

[0003] In recent years, with the continuous development of tissue engineering technology, more and more researchers have begun to focus on the composite application of natural biomaterials and inorganic materials. Adipose-derived matrix bone repair materials have become one of the hot materials in the field of bone repair due to their good biocompatibility and biodegradability. However, single adipose-derived matrix bone repair materials still need improvement in terms of mechanical strength and osteoinductive properties.

[0004] Therefore, there is an urgent need to develop a bone repair material with excellent biocompatibility, osteoinductive properties, and osteoconductive properties. Summary of the Invention

[0005] The present invention solves at least one of the problems of the related art in the following aspects.

[0006] On one hand, the present invention provides a bone repair material, wherein the bone repair material is prepared by pressing a mixture of decellularized adipose matrix fiber, dicalcium phosphate, and aqueous solution into a mold, followed by sterilization and freeze-drying, wherein the decellularized adipose matrix fiber is obtained by preparing decellularized adipose matrix by a supercritical fluid disruption method.

[0007] In some embodiments, the mass ratio of the decellularized adipose matrix fiber to the dicalcium phosphate in the mixed material is 1:(1-10), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, preferably 1:(1.5-2.5), more preferably 1:2.

[0008] In some embodiments, the mass ratio of the total mass of the decellularized adipose matrix fiber and the dicalcium phosphate to the mass of the aqueous solution in the mixed material is 1:(0.5-1.5), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5, preferably 1:1.

[0009] In some embodiments, the particle size D90 of the decellularized adipose matrix fibers is less than 500 μm, for example, it can be less than 490 μm, less than 480 μm, less than 470 μm, less than 460 μm, less than 450 μm or less than 400 μm, and more preferably 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 460, 470, 480, 490 or 500 μm, preferably 30-500 μm.

[0010] In some implementations, the aqueous solution is physiological saline.

[0011] In some embodiments, the aqueous solution is physiological saline with added citrate-sodium citrate buffer or sodium dihydrogen phosphate-disodium hydrogen phosphate buffer at a final concentration of 100 mmol / L.

[0012] In some embodiments, the compression molding pressure is 1-20 MPa, for example, it can be 1-5 MPa, 1-10 MPa, 1-12 MPa, 8-20 MPa, 12-20 MPa, and further can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 MPa.

[0013] In some embodiments, the compression molding pressure is 8-12 MPa.

[0014] In some preferred embodiments, the compression molding pressure is 10 MPa.

[0015] In some embodiments, the sterilization method is irradiation sterilization or ethylene oxide sterilization, preferably irradiation sterilization.

[0016] In some embodiments, the sterilization method is to perform irradiation sterilization with an irradiation dose of 5-40 kGy, for example, 5-20 kGy, 5-25 kGy, 5-30 kGy, 30-40 kGy, 20-30 kGy, 20-25 kGy, 25-30 kGy, 25-40 kGy, 20-40 kGy, and further, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, or 40 kGy.

[0017] In some preferred embodiments, the sterilization method is to perform irradiation sterilization with an irradiation dose of 20-30 kGy, more preferably 25 kGy.

[0018] In some embodiments, the decellularized adipose matrix is ​​obtained by decellularizing adipose tissue using a supercritical fluid method.

[0019] In some embodiments, the decellularized lipid matrix is ​​homogenized at a rotation speed of 11,000-13,000 rpm, for example, 11,000, 11,500, 12,000, 12,500 or 13,000 rpm, preferably 12,000 rpm.

[0020] In some implementations, the supercritical fluid method uses carbon dioxide as a solvent.

[0021] In some embodiments, the supercritical fluid method pressure is 20-25 MPa, for example, 20, 21, 22, 23, 24 or 25 MPa, preferably 22 MPa.

[0022] In some embodiments, the supercritical fluid method temperature is 33-37°C, for example, 33, 34, 35, 36, or 37°C, preferably 36°C.

[0023] In some embodiments, the supercritical fluid carbon dioxide flow rate is 0.09-0.1 L / min, for example, it can be 0.09, 0.091, 0.092, 0.093, 0.094, 0.095, 0.096, 0.097, 0.098, 0.099 or 0.1 L / min, preferably 0.1 L / min.

[0024] In some embodiments, the supercritical fluid method takes 16-24 hours, for example, 16, 17, 18, 19, 20, 21, 22, 23 or 24 hours, preferably 16 hours.

[0025] In some embodiments, a pretreatment step and a sterilization step are further included before the removal of cells from adipose tissue by supercritical fluid method.

[0026] In some implementations, the pretreatment step includes removing impurities from the adipose tissue and washing it for later use.

[0027] In some embodiments, the disinfection step includes disinfecting by mixing a disinfectant with pretreated adipose tissue and agitating.

[0028] In some embodiments, the mass-to-volume ratio of the pretreated adipose tissue to the disinfectant is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, preferably 1:10.

[0029] In some embodiments, the oscillation temperature is 25-30°C, for example, 25, 26, 27, 28, 29 or 30°C, preferably 26°C.

[0030] In some embodiments, the oscillation speed is 150-200 rpm, for example, 150, 160, 170, 180, 190 or 200 rpm, preferably 180 rpm.

[0031] In some implementations, the oscillation time is 4-8 hours, for example, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8 hours, preferably 6 hours.

[0032] In some embodiments, the disinfectant is a solution of peracetic acid and ethanol.

[0033] In some preferred embodiments, the concentration of peracetic acid is 0.02%-2%, for example, it can be 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, or 2%, preferably 0.2%-1%, more preferably 0.2%.

[0034] In some preferred embodiments, the concentration of ethanol is 2%-20%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, preferably 4%-10%, more preferably 4%.

[0035] In some embodiments, the adipose tissue is derived from mammals, preferably humans, sheep, cattle, or pigs, more preferably humans.

[0036] In some embodiments, the porosity of the bone repair material is 30%-80%, for example, it can be 30%, 34%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, preferably 30%-50%.

[0037] In some embodiments, the bone repair material component comprises one or more proteins selected from collagen or vimentin.

[0038] In some embodiments, the collagen comprises one or more selected from type I collagen, type III collagen, type IV collagen, or type VI collagen.

[0039] In some preferred embodiments, the collagen content is not less than 10%, for example, it can be not less than 15%, not less than 20%, not less than 25%, not less than 30%, not less than 35%, and further can be 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%.

[0040] In some embodiments, the vimentin content is not less than 10%, for example, it can be not less than 11%, not less than 12%, not less than 13%, not less than 14%, not less than 15%, and more specifically, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%.

[0041] In some preferred embodiments, the collagen content is 10%-40%.

[0042] In some preferred embodiments, the vimentin content is 10%-20%.

[0043] On the other hand, the present invention provides a method for preparing the above-mentioned bone repair material, wherein the preparation method comprises the following steps:

[0044] (1) Using carbon dioxide as a solvent, cells were removed from sterilized adipose tissue using a supercritical fluid method to obtain decellularized adipose matrix;

[0045] (2) The decellularized lipid matrix is ​​broken down to obtain decellularized lipid matrix fibers;

[0046] (3) The decellularized adipose matrix fiber, calcium hydrogen phosphate and aqueous solution are mixed to obtain a mixed material;

[0047] (4) After the mixed material is pressed into shape, it is sterilized and freeze-dried to obtain the bone repair material.

[0048] Furthermore, the present invention provides the use of the above-mentioned bone repair material or the above-mentioned preparation method in the preparation of biomedical materials or drugs, wherein the biomedical material or drug is used in one or more of the following:

[0049] (1) Repairing bone tissue defects caused by fractures, bone defects, and osteonecrosis;

[0050] (2) Repairing bone defects caused by bone tumor resection;

[0051] (3) Repairing bone defects caused by congenital bone deformities or malformations;

[0052] (4) Repairing tooth defects;

[0053] (5) Bone defect filling and bone reconstruction in orthopedic surgery.

[0054] In another aspect, the present invention provides a product for bone repair, characterized in that it includes the above-mentioned bone repair material or bone repair material prepared by the above-mentioned preparation method, and its instruction manual.

[0055] Advantages of this invention

[0056] (1) The composite bone repair material prepared by the present invention is derived from human adipose tissue and decellularized matrix is ​​obtained through a series of treatments. It is completely humanized. Compared with animal-derived tissue matrix, human-derived material has good biocompatibility, which greatly reduces the immune rejection and inflammatory response in the body after material implantation, and improves the patient's comfort and treatment effect.

[0057] (2) The preparation process of this invention does not use enzyme digestion or organic reagent extraction to process raw materials, thus avoiding the problems of solvent residue and environmental pollution. In addition, the decellularized matrix material will not introduce toxic chemicals or residues, making the final material safer.

[0058] (3) The present invention achieves a very good oil removal extraction effect by pretreatment with disinfection step, combined pretreatment with ethanol and peracetic acid, and then supercritical carbon dioxide extraction. Compared with enzyme digestion and fat ultrasonic pretreatment, this process is easier to scale up, has lower cost, and can achieve better extraction effect.

[0059] (4) By controlling the particle size of the matrix particles and the magnitude of the pressing pressure, the water stability (water resistance) of the composite material can be controlled. Through these physical properties, the in vivo stability of the bone repair material can be extended, providing an ideal long-term microenvironment for the attachment and proliferation of bone cells.

[0060] Finally, this material can broaden its application scope. Because the bone repair material prepared by this invention has excellent biocompatibility, bioactivity, and safety, its application range is very wide. In addition to its use in traditional fields such as fracture repair, bone defect repair, and osteonecrosis treatment, its application potential in orthopedic surgery, plastic surgery, and dentistry can be further explored. Attached Figure Description

[0061] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0062] Figure 1A This is a schematic diagram of the preparation process of the decellularized fat matrix bone repair material in Example 1.

[0063] Figure 1B This is an image of the decellularized matrix bone repair material prepared in Example 1.

[0064] Figure 2 This is an electron microscopy scan of the decellularized adipose-derived bone repair material from Example 1.

[0065] Figure 3 To examine the treatment effect of decellularized adipose-derived matrix bone repair material in Case 4 on bone defect.

[0066] To facilitate understanding of the present invention, the implementation process of the present invention will be further described below with reference to specific embodiments. These descriptions are only for further illustrating the features and advantages of the present invention, and are not intended to limit the scope of the claims. Detailed Implementation

[0067] The present invention will now be described in further detail with reference to specific embodiments. The embodiments given are merely illustrative of the invention and are not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.

[0068] I. Definition

[0069] In this invention, unless otherwise stated, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Furthermore, the related terms and laboratory procedures used herein are all widely used terms and routine procedures in the respective fields. To better understand this invention, definitions and explanations of related terms are provided below.

[0070] As used herein and unless otherwise stated, the terms “about” or “approximately” mean within 10% of a given value or range. Where an integer is required, the term means within 10% of a given value or range, rounded up or down to the nearest integer.

[0071] In the description herein, references to “some embodiments,” “some implementations,” or “some implementation schemes” describe a subset of all possible embodiments. However, it is understood that “some embodiments” may be the same subset or different subsets of all possible embodiments and may be combined with each other without conflict.

[0072] As used herein, the terms “comprising,” “including,” “having,” and “containing” are open-ended expressions, meaning they include the contents specified in this invention but do not exclude other aspects.

[0073] As used herein, the terms “optional,” “any,” “arbitrary,” or “any one” mean that the event or situation described below may, but does not have to, occur, including the circumstances in which the event or situation occurs or does not occur. As used herein, “an” and “a” refer to one or more grammatical objects.

[0074] As used herein, the term “and / or” should be understood to mean any one of the options or any combination of two or more of the options.

[0075] Throughout this specification, when a section “comprises” / “contains” a component, unless otherwise expressly stated, it means that it may also include other components rather than excluding them. When permissible manufacturing and material tolerances (which are inherent in their meaning) are presented, the terms “about” or “substantially” are used in or near numerical values. These terms are intended to prevent unscrupulous infringers from improperly using the disclosure, where accurate or absolute values ​​are cited to aid in understanding the invention.

[0076] As used herein, the term "supercritical fluid method" is an extraction and separation technique that uses a supercritical fluid—a fluid in a thermodynamic state above its critical temperature and pressure—as an extractant to extract specific components from a liquid or solid to achieve separation. In some embodiments, the extractant is carbon dioxide.

[0077] II. Examples

[0078] The present invention will be described in detail below through specific embodiments. It should be understood that the following embodiments are for explanation and illustration only and do not limit the scope of the present invention in any way.

[0079] Materials and equipment not specifically described in the specific embodiments of this disclosure can be obtained by purchasing commercially available products.

[0080] Example 1

[0081] This embodiment provides a method for using decellularized matrix bone repair material from human adipose tissue. The fat is obtained through aspiration or surgical removal (from Shanghai Ninth People's Hospital, donated by a liposuction patient with informed consent). The overall process is as follows: Figure 1A As shown, the specific steps include:

[0082] 1.1 Adipose tissue cleaning: Collect fresh adipose tissue samples, let them stand for 20 minutes to separate into layers, remove the blood water from the fat, and then use a cleaning solution to stir and clean the adipose tissue. Repeat this process 5 times to obtain clean adipose tissue.

[0083] 1.2 Pretreatment of adipose tissue: The clean adipose tissue obtained in step 1.1 was subjected to fascia removal and vascular tissue removal, leaving only adipose granules.

[0084] 1.3 Disinfection of adipose tissue (virus inactivation): Take 1L of pretreated adipose tissue particles, add disinfectant (0.2% peracetic acid and 4% ethanol) at a material-to-liquid ratio of 1:10, mix and shake, set the shaker temperature to 26℃ and the speed to 180rpm, and treat for 6 hours.

[0085] 1.4 Decellularization of adipose tissue: The sterilized fat was placed in a reactor, and gaseous carbon dioxide was pumped in under high pressure to prepare a supercritical fluid. The pressure was maintained at 22 MPa, the temperature at 36 °C, and the carbon dioxide flow rate at 0.1 L / min for 16 h. Then the pressure of the reactor was reduced to atmospheric pressure, and the extracted adipose tissue was taken out for the next homogenization step.

[0086] 1.5 Matrix crushing and grinding: The product obtained in step 1.4 was homogenized at high speed in a homogenizer at a speed of 12000 rpm for 5 min, and repeated 3 times. After sieving, matrix fiber material with a particle size of less than 500 micrometers was obtained.

[0087] 1.6 Compound preparation (inorganic salt mixture): Take 40g of sieved matrix fiber material with a dry weight of 2.53g, add 5.06g of dicalcium phosphate at a mass ratio of 1:2, then add 7ml of physiological saline, mix well to obtain a paste-like matrix material.

[0088] 1.7 Molding (pressing): Pour the mixed paste matrix into a mold and apply a pressure of 10 MPa to make it into a cylindrical or block shape.

[0089] 1.8 Sterilization (irradiation sterilization): The molded matrix phosphate composite material is sterilized by irradiation with a dose of 25 kGy.

[0090] 1.9 Freeze-drying: The irradiated sterilized matrix phosphate composite material is freeze-dried to remove moisture and fix its shape, resulting in a freeze-dried solid, which is the decellularized fat matrix bone repair material.

[0091] The decellularized fat matrix bone repair material prepared in this embodiment is described in [reference needed]. Figure 1B After a series of process steps, the material can be stably shaped. Figure 2 The scanning electron microscopy results of the decellularized adipose-derived matrix bone repair material prepared in this embodiment are as follows: Figure 2 As can be seen, the decellularized matrix bone repair material exhibits a good porous structure.

[0092] In this embodiment, the acellular adipose-derived matrix bone repair material was prepared by lysing the sample with 0.5 mol / L NaOH solution for 4 hours, adjusting the pH to 8 with hydrochloric acid solution, and then adding trypsin for 16 hours to completely digest the adipose-derived matrix sample. Subsequently, label-free LC MS / MS was used to accurately identify and relatively quantify the proteins in the supernatant of the digested sample. Then, GeneOntology (GO) analysis was performed on the identified proteins to determine the specific tissue and cellular localization of each protein, and the relative abundance ratio of each protein to each category was calculated.

[0093] Data analysis using proteomics software revealed the main protein components (mass content higher than 1%), as shown in Table 1. Table 1 shows that the main component of the decellularized adipose-derived bone repair material is collagen, primarily type I collagen, followed by types VI, III, and IV collagen. Collagen accounts for 39.9% of the total protein content, followed by vimentin.

[0094] Table 1

[0095] Collagen α-2(I) chain 13.79 Vimentin 12.66 Collagen α-1(I) chain 7.27 Collagen α-3(VI) chain 5.29 albumin 4.54 Collagen α-2(VI) chain 4.17 Collagen α-1(III) chain 3.5 apolipoprotein 3 Collagen α-2(IV) chain 2.98 Collagen α-1(VI) chain 2.9 Carbonic anhydrase 2.57 transmembrane protease 13 1.75 Actin 1.45 flavin reductase 1.15 Amine oxidase 1.14

[0096] Example 2

[0097] The paste-like matrix material obtained in step 1.7 of Example 1 was poured into a mold, and pressures of 0 MPa, 1 MPa, 10 MPa, and 20 MPa were applied to make it into a cylindrical or block shape. Then, it was sterilized by 25 KGy irradiation and freeze-dried to prepare four groups of bone repair materials with different densities (CEFFE GEL-0 MPa, CEFFE GEL-1 MPa, CEFFE GEL-10 MPa, CEFFE GEL-20 MPa).

[0098] As shown in Table 2, the bone repair materials under all pressure conditions maintained their shape stability in saline solution without disintegration or loosening. Only under the 1 MPa pressure condition did a small portion loosen on day 7. If the bone repair material cannot maintain a stable shape, subsequent bone cell adhesion and growth will be affected, which in turn will impact bone repair at the fracture site. Therefore, pressure conditions of 1-20 MPa are sufficient.

[0099] Table 2. Density, porosity, and integrity of bone repair materials under different pressure conditions.

[0100]

[0101]

[0102] Comparative Example 1

[0103] The disinfection step in step 1.3 of Example 1 was replaced with the method disclosed in patent CN113365672A. The washed fat was treated with ultrasound at 500W power for 6-12 minutes, and then the fat tissue was shredded by homogenizer at a speed of 6000-18000rpm. After centrifugation, supercritical extraction was performed, and the steps were the same as 1.4-1.9, to obtain the bone repair material, which is Sample-1.

[0104] The decellularization method in step 1.4 of Example 1 was modified to use isopropanol, specifically, the volume ratio of isopropanol to adipose tissue block was 10:1, ensuring the adipose tissue was completely immersed in isopropanol. The reaction vessel was sealed and placed on a shaker for treatment at room temperature. The shaking speed could be set to 150 rpm, and the treatment time was 6 hours. After decellularization, the matrix was washed, and subsequent operations were performed according to steps 1.5-1.9 of Example 1 to obtain the bone repair material, Sample-2.

[0105] The disinfection step in step 1.3 of Example 1 was replaced with enzymatic digestion. Specifically, 0.25% trypsin solution was added to the adipose tissue at a ratio of 1:2. The adipose tissue trypsin solution was slowly stirred (60 rpm) and digested at 37°C for 6 hours. After washing the adipose tissue with physiological saline, supercritical extraction was performed, with the same steps as 1.4-1.9, to obtain the bone repair material, which is Sample-3.

[0106] The disinfection step in step 1.3 of Example 1 was removed, and the supercritical extraction step was performed directly after the pretreatment step. The steps were the same as those in 1.4-1.9, and the bone repair material, Sample-4, was obtained.

[0107] Comparative Example 2

[0108] In Example 1, the calcium hydrogen phosphate compounded in step 1.6 was replaced with calcium sulfate or calcium carbonate and compounded with decellularized adipose matrix fibers, while the parameters of the other steps remained unchanged, to obtain bone repair materials (CEFFE GEL-CaSO4, CEFFE GEL-CaCO3).

[0109] Comparative Example 3

[0110] The matrix particles obtained in step 1.5 of Example 1 were sieved into different particle size ranges, specifically particles smaller than 500-1000 μm and larger than 1000 μm. The decellularized matrix particles of different sizes were then compounded with calcium hydrogen phosphate, and the remaining steps remained unchanged to obtain bone repair materials (CEFFE GEL-M, CEFFE GEL-L).

[0111] Detection Example 1

[0112] The decellularized adipose matrix obtained by each method in Example 1 and Comparative Example 1 was weighed before matrix disruption to determine the quality of the matrix.

[0113] Referring to the method in GB5009.6-1985, the residual fat in the bone repair materials prepared by each method in Example 1 and Comparative Example 1 was detected. The bone repair material samples were placed in a Soxhlet extractor and extracted by reflux with anhydrous diethyl ether or petroleum ether, or other organic solvents. The organic solvent was continuously evaporated, condensed, and refluxed back into the extractor to ensure the fat was fully dissolved in the solvent. After extraction, the solvent was evaporated, and the weight of the remaining material was measured. The fat content was calculated by the weight difference before and after extraction.

[0114] When decellularized matrix is ​​used for medical purposes such as tissue repair, residual fat may trigger an immune response. Certain components of fat, such as lipid antigens, can be recognized as foreign substances by the body's immune system. This immune system activates immune cells, leading to an inflammatory response in the local tissue. Severe inflammation can impede the tissue repair process. Furthermore, residual fat can reduce the biocompatibility of the material. For example, in bone repair materials, excessive residual fat can hinder integration with the surrounding bone tissue.

[0115] Ethanol is an organic solvent that can dissolve some fat-soluble components in adipose tissue. Peracetic acid can oxidize certain components in adipose tissue, altering the structure of fat molecules and increasing their polarity. This structural change makes fats more readily interact with carbon dioxide during subsequent supercritical carbon dioxide extraction, as supercritical carbon dioxide has a better extraction effect on highly polar substances.

[0116] As shown in Table 4, pre-treatment with supercritical carbon dioxide (SCCO) and supercritical carbon dioxide extraction alone yielded similar matrix yields, and the residual fat in the material was significantly lower than that obtained by supercritical carbon dioxide extraction alone (Examples 1 and Sample-4). Regarding matrix yield, the yield in Example 1 was significantly higher than that in Comparative Examples 1 (Sample-1, Sample-2, and Sample-3). This is because high-speed homogenization and grinding result in the loss of most soluble proteins, trypsin digestion also leads to a significant loss of matrix proteins, and the organic solvent extraction step also causes substantial protein denaturation and loss. The residual fat in Example 1 was significantly lower than that in the Comparative Examples, indicating that the sterilization step effectively promotes the oil extraction effect of supercritical carbon dioxide.

[0117] Table 4. Detection of residual fat and yield of decellularized fat matrix in bone repair materials prepared by different methods.

[0118] Matrix yield (g / L) 4.51 1.16 2.51 1.37 4.91 Residual fat (g / 100g) 0.15 1.76 1.63 1.11 3.69

[0119] Detection Example 2

[0120] After collagen is hydrolyzed by collagenase, hydroxyproline in its structure is released. Using a kit (catalog number: BC0250, brand: Solarbio) with colorimetric reactions, the absorbance is measured at a specific wavelength of 550 nm using a spectrophotometer. The hydroxyproline content is calculated based on a standard curve, thus reflecting the amount of collagen. The bone repair materials obtained in Example 1 and Comparative Example 2 were cut into 5 mm cubes and placed in 1 ml of type I collagenase solution (0.5 mg / ml, pH 7.2). The hydroxyproline content in the enzyme solution was measured after 1 day and 3 days. The hydroxyproline content in the solution indirectly reflects the amount of hydrolyzed collagen and also indirectly indicates the stability of the bone repair material.

[0121] During bone repair, decellularized matrix bone repair materials need to integrate well with the host bone tissue. If the material degrades too quickly, it will disappear in large quantities before a stable chemical bond and tissue connection can be formed between the material and the bone tissue. This leads to poor stability of the material-host bone interface, making it difficult for new bone to attach and grow, thus affecting the quality of bone repair. The results, as shown in Table 5, indicate that under the same pressure (10 MPa), the collagenase degradation rate of calcium sulfate bone repair materials was significantly higher than that of calcium carbonate bone repair materials. The rate was 2.2 times that of calcium sulfate and 2.8 times that of calcium carbonate, demonstrating that calcium phosphate has a significant advantage among inorganic salts used in the preparation of bone repair materials.

[0122] Table 5. Collagen degradation test results of different bone repair materials

[0123] Day 1 Hydroxyproline content (μg / ml) 5.4 8.9 10.7 Day 3 Hydroxyproline content (μg / ml) 35.4 80.2 98.7

[0124] Detection Example 3

[0125] The bone repair materials prepared by the methods in Example 1 and Comparative Example 3 were added to physiological saline at a volume ratio of 1:20 and placed in a 37°C constant temperature incubator to simulate the shape maintenance performance, i.e., water resistance, of the materials in the human body. The shape of the bone repair materials was observed on days 1, 3, and 7. The results are shown in Table 6. When the bone repair materials were placed in physiological saline, the larger the decellularized matrix particles, the less stable the material. Materials with a particle size greater than 1000 μm completely dissolved on day 3, bone repair materials with a particle size of 500-1000 μm completely dissolved on day 7, and bone repair materials with a particle size less than 500 μm remained intact on day 7. The inability of the bone repair materials to maintain a stable shape will affect subsequent bone cell adhesion and growth, which in turn will affect bone repair at the fracture site.

[0126] Table 6. Water resistance test results of different bone repair materials

[0127] Day 1 whole whole whole Day 3 whole whole Partially dissolved and loose Day 7 whole A small portion dissolved and loose Completely dissolved and loose

[0128] Example 4. The therapeutic effect of decellularized adipose-derived bone repair material on bone defects in rats.

[0129] Nine male SD rats (obtained from Beijing Vital River Laboratory Animal Technology Co., Ltd.) weighing 220-270g were selected for the experiment. For 12 hours prior to surgery, all SD rats were fasted and deprived of water. On the day of surgery, anesthetic drugs were administered according to the rats' weight for general anesthesia. The rats' vital signs were closely monitored. After their breathing stabilized, the rats were fixed in a prone position on the operating table. The prepared skin area was treated with depilatory cream, shaved, and iodine-soaked cotton balls were applied to the prepared area from the inside out. Routine disinfection was performed, and the area was draped. A longitudinal incision of approximately 2-2.5cm was made along the midline of the rat's skull using a medical marker. The sagittal suture and at least 6mm of the bilateral parietal bones were fully exposed using surgical instruments. The periosteum was separated, and bilateral full-thickness skull defects of 5mm in diameter were prepared, avoiding the midcranial suture. The skull section of the defect area was polished with a fine-tipped drill. Gently rinse both sides of the skull defect area with an appropriate amount of saline solution to avoid leaving bone fragments or debris in the surgical area.

[0130] In rats with skull defects, the control group received bone repair material without the preparation of Example 1, while the experimental group received bone repair material prepared in Example 1. The periosteum, subcutaneous tissue, and skin were sutured layer by layer with 3-0 silk sutures, and the wound was treated with povidone-iodine. Each rat was injected intramuscularly with penicillin in its hind leg for 3 days to prevent infection. The rats were closely observed for any abnormalities in their postoperative physiological and mental activity, any signs of suture detachment, and the wound healing process.

[0131] Four weeks later, the rats were humanely euthanized, the rat skulls were removed, a large amount of soft tissue was removed, and the skulls were fixed in 10% formalin solution for 48 hours. Routine Micro-CT imaging was performed to observe the defective areas, and frontal Micro-CT radiographs were taken to observe the defective areas. Figure 3 In the figures, A and B represent the blank control group and the bone repair material group from Example 1, respectively. Figure 3 As shown in Figure A, it can be seen that only a very small amount of new bone formation was observed at the skull defect site in the control group rats; Figure 3 Figure B shows that the defect in the transplanted bone repair material of Example 1 was filled with new bone after only 4 weeks.

[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this disclosure, and are not intended to limit them. Although this disclosure has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this disclosure.

[0133] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0134] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A bone repair material, wherein, The bone repair material is prepared by pressing a mixture of decellularized adipose matrix fibers, calcium hydrogen phosphate, and an aqueous solution into shape, followed by sterilization and freeze-drying. The decellularized adipose matrix fibers are obtained by breaking down adipose matrix using a supercritical fluid method. The aqueous solution is physiological saline. The mass ratio of the decellularized adipose matrix fibers to the calcium hydrogen phosphate is 1:(1-10). The decellularized adipose matrix fiber particle size D90 is less than 500 μm. The pressure for compression molding is 1-20 MPa.

2. The bone repair material according to claim 1, wherein, In the mixed material, the mass ratio of the decellularized adipose matrix fiber to the calcium hydrogen phosphate is 1:(1.5-2.5).

3. The bone repair material according to claim 2, wherein, In the mixed material, the mass ratio of the decellularized adipose matrix fiber to the calcium hydrogen phosphate is 1:

2.

4. The bone repair material according to claim 1, wherein, In the mixed material, the total mass of the decellularized adipose matrix fiber and the calcium hydrogen phosphate is in the mass ratio of the aqueous solution to 1:(0.5-1.5).

5. The bone repair material according to claim 4, wherein, In the mixed material, the total mass ratio of the decellularized adipose matrix fiber and the calcium hydrogen phosphate to the mass ratio of the aqueous solution is 1:

1.

6. The bone repair material according to claim 1, wherein, The particle size D90 of the decellularized adipose matrix fiber is 30-500 μm.

7. The bone repair material according to claim 1, wherein, The aqueous solution is physiological saline with added citrate-sodium citrate buffer or sodium dihydrogen phosphate-disodium hydrogen phosphate buffer at a final concentration of 100 mmol / L.

8. The bone repair material according to claim 1, wherein, The pressure for compression molding is 8-12 MPa.

9. The bone repair material according to claim 8, wherein, The pressing pressure is 10 MPa.

10. The bone repair material according to claim 1, wherein, The sterilization method is irradiation sterilization or ethylene oxide sterilization.

11. The bone repair material according to claim 10, wherein, The sterilization method is irradiation sterilization.

12. The bone repair material according to claim 11, wherein, The sterilization method is to perform irradiation sterilization with an irradiation dose of 5-40 kGy.

13. The bone repair material according to claim 12, wherein, The sterilization method is to perform irradiation sterilization with an irradiation dose of 20-30 kGy.

14. The bone repair material according to any one of claims 1-13, wherein, The decellularized adipose matrix was obtained by removing cells from adipose tissue using a supercritical fluid method.

15. The bone repair material according to claim 14, wherein, The decellularized lipid matrix was homogenized and broken up at a rotation speed of 11,000-13,000 rpm.

16. The bone repair material according to claim 14, wherein, The supercritical fluid method uses carbon dioxide as a solvent.

17. The bone repair material according to claim 14, wherein, The pressure for the supercritical fluid method is 20-25 MPa.

18. The bone repair material according to claim 14, wherein, The supercritical fluid method has a temperature of 33-37℃.

19. The bone repair material according to claim 16, wherein, The supercritical fluid method has a carbon dioxide flow rate of 0.09-0.1 L / min.

20. The bone repair material according to claim 14, wherein, The supercritical fluid method takes 16-24 hours.

21. The bone repair material according to claim 14, wherein, Prior to removing cells from adipose tissue using the supercritical fluid method, a pretreatment step and a sterilization step are further included.

22. The bone repair material according to claim 21, wherein, The pretreatment step includes removing impurities from the adipose tissue and washing it for later use.

23. The bone repair material according to claim 21, wherein, The disinfection step includes mixing the disinfectant with pretreated adipose tissue and agitating to disinfect it.

24. The bone repair material according to claim 23, wherein, The mass-to-volume ratio of the pretreated adipose tissue to the disinfectant is 1:(10-20).

25. The bone repair material according to claim 23, wherein, The oscillation temperature is 25-30℃.

26. The bone repair material according to claim 23, wherein, The oscillation speed is 150-200 rpm.

27. The bone repair material according to claim 23, wherein, The oscillation time is 4-8 hours.

28. The bone repair material according to claim 23, wherein, The disinfectant is a solution of peracetic acid and ethanol.

29. The bone repair material according to claim 28, wherein, The concentration of peracetic acid is 0.02%-2%.

30. The bone repair material according to claim 29, wherein, The concentration of peracetic acid is 0.2%-1%.

31. The bone repair material according to claim 29, wherein, The concentration of peracetic acid is 0.2%.

32. The bone repair material according to claim 28, wherein, The concentration of the ethanol is 2%-20%.

33. The bone repair material according to claim 32, wherein, The concentration of the ethanol is 4%-10%.

34. The bone repair material according to claim 32, wherein, The concentration of the ethanol is 4%.

35. The bone repair material according to claim 21, wherein, The adipose tissue is derived from mammals.

36. The bone repair material according to claim 35, wherein, The adipose tissue is derived from humans, sheep, cattle, or pigs.

37. The bone repair material according to claim 35, wherein, The adipose tissue is derived from humans.

38. The bone repair material according to claim 1, wherein, The porosity of the bone repair material is 30%-80%.

39. The bone repair material according to claim 38, wherein, The porosity of the bone repair material is 30%-50%.

40. The bone repair material according to claim 1, wherein, The bone repair material contains one or more components selected from collagen or vimentin.

41. The bone repair material according to claim 40, wherein, The collagen includes one or more types selected from type I, type III, type IV, or type VI collagen.

42. The bone repair material according to claim 40, wherein, The collagen content is not less than 10%.

43. The bone repair material according to claim 40, wherein, The vimentin content is not less than 10%.

44. The bone repair material according to claim 42, wherein, The collagen content is 10%-40%.

45. The bone repair material according to claim 43, wherein, The vimentin content is 10%-20%.

46. ​​A method for preparing the bone repair material according to any one of claims 1-45, wherein, The preparation method includes the following steps: (1) Using carbon dioxide as a solvent, cells were removed from sterilized adipose tissue using a supercritical fluid method to obtain decellularized adipose matrix; (2) The decellularized lipid matrix is ​​broken down to obtain decellularized lipid matrix fibers; (3) The decellularized adipose matrix fiber, calcium hydrogen phosphate and aqueous solution are mixed to obtain a mixed material; (4) After the mixed material is pressed into shape, it is sterilized and freeze-dried to obtain the bone repair material.

47. Use of the bone repair material according to any one of claims 1-45 or the preparation method according to claim 46 in the preparation of biomedical materials or drugs, wherein, The biomedical material or drug is used for one or more of the following: (1) Repairing bone tissue defects caused by fractures, bone defects, and osteonecrosis; (2) Repairing bone defects caused by bone tumor resection; (3) Repairing bone defects caused by congenital bone deformities or malformations; (4) Repairing tooth defects; (5) Bone defect filling and bone reconstruction in orthopedic surgery.

48. A product for bone repair, characterized in that, Includes the bone repair material according to any one of claims 1-45 or the bone repair material prepared by the preparation method according to claim 46, and its description.

Citation Information

Patent Citations

  • Bone repair composite material based on acellular biological tissue matrix material and preparation method of bone repair composite material

    CN105412989A

  • Method for extracting extracellular matrix using supercritical fluid, and extracellular matrix biomaterial for tissue regeneration produced thereby

    CN113365672A